2012
DOI: 10.1186/1742-6405-9-18
|View full text |Cite
|
Sign up to set email alerts
|

Virological effectiveness and CD4+ T-cell increase over early and late courses in HIV infected patients on antiretroviral therapy: focus on HCV and anchor class received

Abstract: BackgroundThe aim of this study was to explore the effects of HCV co-infection on virological effectiveness and on CD4+ T-cell recovery in patients with an early and sustained virological response after HAART.MethodsWe performed a longitudinal analysis of 3,262 patients from the MASTER cohort, who started HAART from 2000 to 2008. Patients were stratified into 6 groups by HCV status and type of anchor class. The early virological outcome was the achievement of HIV RNA <500 copies/ml 4–8 months after HAART initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…After a given cART achieves an undetectable HIV viral load, we think that the influence of the drug used might be secondary except for the side effects that may result in poorer adherence. (iii) HCV infection has also an influence on CD4+ T‐cell recovery . In our study, around 30% of the patients had HCV infection at baseline and no patient was treated in the analysed follow‐up period.…”
Section: Discussionmentioning
confidence: 60%
“…After a given cART achieves an undetectable HIV viral load, we think that the influence of the drug used might be secondary except for the side effects that may result in poorer adherence. (iii) HCV infection has also an influence on CD4+ T‐cell recovery . In our study, around 30% of the patients had HCV infection at baseline and no patient was treated in the analysed follow‐up period.…”
Section: Discussionmentioning
confidence: 60%
“…HCV/HIV is also causing health burden worldwide [3, 4]. Despite extensive research and subsequently better understanding of the negative effects of HIV infection on HCV replication, persistence and liver fibrogenesis [5-8], whether HCV is associated with HIV progression continues to be debated.…”
Section: Introductionmentioning
confidence: 99%
“…However, inconsistent results have been reported for CD4 and HIV virologic responses to ART as well as HIV progression and mortality. While some studies have shown that HCV co-infection is associated with either smaller CD4 increases after initiation of ART [11-16] or a delayed CD4 response [17], other studies report early detected differences in CD4 response wane over time [4, 18]. Many studies have not found such an association [3, 19-25].…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] For other factors, particularly for low CD4, which was a significant predictor of quantifiable viral load in univariate analyses, the limited sample size may have reduced the power to maintain statistical significance in the multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%